Spiritual Resilience as Immunity to Stress during COVID-19 Pandemic: A Sociological Perspective - Fauziah, Meli; Octavia, Vera (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This study examines spiritual resilience from a sociological standpoint and as a sort of immunization against stress during pandemic times. The Piedmont theory of the spiritual dimension was used in this study to address the question of how the mental health of the stay-at-home mother was impacted by spiritual resilience, and George Herbert Mead's theories of symbolic interactionism were used as an analytical tool to examine spiritual resistance from a sociological perspective. By gathering samples from household mothers in the Cirebon district, the study employs a qualitative descriptive method of case studies. The findings indicate that household mothers' mental health was significantly impacted by their spiritual endurance. By having spiritual resilience, household mothers could give positive meanings to their social thoughts and actions. This article attempts to make a significant contribution to the study of the role of household mothers in facing the challenges and stresses of pandemic times.